2018
DOI: 10.1071/rd17467
|View full text |Cite
|
Sign up to set email alerts
|

Effect of counting chamber depth on the accuracy of lensless microscopy for the assessment of boar sperm motility

Abstract: Sperm motility is one of the most significant parameters in the prediction of male fertility. Until now, both motility analysis using an optical microscope and computer-aided sperm analysis (CASA-Mot) entailed the use of counting chambers with a depth to 20µm. Chamber depth significantly affects the intrinsic sperm movement, leading to an artificial motility pattern. For the first time, laser microscopy offers the possibility of avoiding this interference with sperm movement. The aims of the present study were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 80 publications
(87 reference statements)
0
30
0
3
Order By: Relevance
“…Initially, tracking of spermatozoa in three dimensions was performed by high-speed image stack acquisitions in sea urchin spermatozoa (Corkidi et al 2008) and a lens-free on-chip imaging technique in human spermatozoa (Su et al 2012) and boar (Soler et al 2018) spermatozoa. Newly developed CASA software enables the modelling and simulation of fourdimensional sperm motility tracks from the x and y coordinates obtained from normal two-dimensional tracks ( Fig.…”
Section: Four-dimensional Motilitymentioning
confidence: 99%
“…Initially, tracking of spermatozoa in three dimensions was performed by high-speed image stack acquisitions in sea urchin spermatozoa (Corkidi et al 2008) and a lens-free on-chip imaging technique in human spermatozoa (Su et al 2012) and boar (Soler et al 2018) spermatozoa. Newly developed CASA software enables the modelling and simulation of fourdimensional sperm motility tracks from the x and y coordinates obtained from normal two-dimensional tracks ( Fig.…”
Section: Four-dimensional Motilitymentioning
confidence: 99%
“…En función de la especie y el estado fisiológico, se necesita un espacio considerable para desarrollar correctamente la movilidad espermática, debido a que el movimiento natural de los espermatozoides es helicoidal (Kraemer et al, 1998;Soler et al, 2018). En la literatura veterinaria, la altura de la cámara de recuento para el análisis de la cinética y movilidad del semen es variable y por lo general, no se suele mencionar (Hoogewijs et al, 2012).…”
Section: Discussionunclassified
“…Several authors have indicated that the results are dependent on the set‐up of the system used, such as the field of observation location (Nöthling & dos Santos, ), frame rate of recordings (Wilson‐Leedy & Ingermann, ), the kind and depth of the counting chamber used, the volume of the drop and other factors (Bompart et al., ; Soler et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect is that the correct determination of sperm tracks results in a fundamental shift in the determination of motility and morphology subpopulation structure. The fact that an ejaculate is constituted of different subpopulations of spermatozoa has been well established in a great variety of species (boar (Abaigar, Holt, Harrison, & del Barrio, ; Flores et al., ; Holt, Holt, & Moore, ; Soler et al., ), bull (Valverde et al., ; Yániz et al., ), donkey (Flores et al., ), eel (Gallego et al., ), fox (Soler et al., , ), gazelle (Abaigar et al., ), goat (Vázquez et al., ), ram (Luna et al., ), stallion (Ortega‐Ferrusola et al., ), human (Vásquez, Soler, Camps, Valverde, & García‐Molina, ; Yániz et al., ), salmon (Caldeira et al., )), but most of these studies were not designed for considering the effect of the FR.…”
Section: Introductionmentioning
confidence: 99%